Índice de vulnerabilidade a desastres relacionados com fenômenos naturais no município de João Pessoa, Paraíba, Brasil - Azevêdo, Bianca Maria Limeira de (2020)
The disordered urbanization of the city of João Pessoa – PB and the intense daily rainfall have caused extensive damage to the population, especially to those who are exposed and vulnerable to the threat of such phenomena. Evaluating the vulnerability of societies is necessary in order to identify and correct their root causes and to build resilient cities. For that purpose, a wider vulnerability assessment is requires, one that includes environmental and socioeconomic aspects. Several vulnerability assessment methods are currently being used on a global and national scale, as well as at the local level. However, local-scale studies are needed because of their effectiveness in helping decision-making processes. This research aims to analyze the vulnerability to hydro meteorological disasters such as flooding, overflow and landslide in neighborhoods and sectors of João Pessoa, employing a vulnerability assessment framework which includes a three-element structure: Susceptibility, Coping and Adaptation, and subsequent calculation of Vulnerability Index (IV) of the districts of the municipality. Secondary data from census tracts were used to quantify the Vulnerability Index, used to identify the most vulnerable sectors and their main needs for vulnerability reduction. Data collected from SIDRA (Auto Recovery IBGE System) database and also from the Public Departments and city’s Civil Defense were used in the study. At neighborhood level, São José has obtained the highest vulnerability, with an IV value equal to 0.816, which is classified as very high; at sectoral level, the West Zone had the highest average IV value, 0.602, classified as high. It was concluded that, as a trend, disaster prone areas match those that are more vulnerable. The index drafted in this study proved to be broad, being able to support municipal managers in decision-making processes, acting in accordance with the urgent needs of each area of the municipality, not only in moments of intense precipitation, but mainly with preventive actions that can make these sites more resilient to disasters.